2015
DOI: 10.1093/ehjci/jev211
|View full text |Cite
|
Sign up to set email alerts
|

Interstudy heterogeneity of definitions of diastolic dysfunction severely affects reported prevalence

Abstract: AimsThe aim of this article is to examine how the European Association of Cardiovascular Imaging (EACVI) and the American Society of Echocardiography (ASE) recommendations on the classification of diastolic dysfunction (DDF) are interpreted in the scientific community and to explore how variations in the DDF definition affect the reported prevalence.Methods and resultsA systematic review of studies citing the EACVI/ASE consensus document ‘Recommendations for the evaluation of left ventricular diastolic functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 23 publications
2
23
1
Order By: Relevance
“…In our fourth study, we found that 22% (54/247) of patients had signs of high preoperative LV filling pressures. This proportion might appear somewhat low, compared to those reported in other studies 61,142,143 . This discrepancy could be due to differences in cohorts, the types of procedure, referral patterns, and different indices used for classifying diastolic dysfunction 56 .…”
Section: Diastolic Dysfunction Nt-probnp and Phfcontrasting
confidence: 67%
“…In our fourth study, we found that 22% (54/247) of patients had signs of high preoperative LV filling pressures. This proportion might appear somewhat low, compared to those reported in other studies 61,142,143 . This discrepancy could be due to differences in cohorts, the types of procedure, referral patterns, and different indices used for classifying diastolic dysfunction 56 .…”
Section: Diastolic Dysfunction Nt-probnp and Phfcontrasting
confidence: 67%
“…26,45,48,81Y84 The same is not true for the diagnosis of diastolic dysfunction 81,85 since there is a substantial heterogeneity in defining diastolic dysfunction even among cardiologists. The measurement of diastolic dysfunction requires expertise and training beyond the scope of a qualitative or semiqualitative examination 86,87 .…”
Section: Global Heart Function and Ventricular Sizementioning
confidence: 99%
“…Selmeryd et al examined how the classifications of DD by the European Association of Cardiovascular Imaging and the American Society of Echocardiography are used and how these variations affect the reported prevalence of DD in the community. 96 The problem with the European Association of Cardiovascular Imaging/American Society of Echocardiography algorithms is that there are no guidelines to deal with discordant measurements, leading to confusion when cardiologists were given the same premeasured variables. 97,98 There were also large differences in HFPEF…”
Section: Differential Diagnosismentioning
confidence: 99%
“…They also found that others did not grade the severity of DD or HFPEF. 96 The other problem with the algorithm is that there is no guidance on how the parameters in the algorithm should be weighed.…”
mentioning
confidence: 99%